Clinical investigation of feline lower urinary tract disease, pathogenic bacteria and their antibiotic sensitivity at University Veterinary Hospital, Universiti Putra Malaysia - Mazda, Delna; Lau, Seng Fong; Omar, Sharina (Chulalongkon University, 2023)
This study describes the clinical manifestation, bacterial pathogens and antibiotic sensitivity in cats diagnosed with Feline lower urinary tract disease (FLUTD). A total of 61 cats diagnosed with FLUTD from 2018 to 2019 were included in this study. Medical records were reviewed and rational antibiotic therapy was calculated from the data collected on antibiotic sensitivity. Most cats in this study belonged to indoor multi-cat households with shared facilities. Thirty-two cats (52.45%) had positive urine cultures and were diagnosed with urinary tract infections. Staphylococcus species (23.2%), Enterococcus species (17.9%) and Escherichia coli (16.1%) were the most isolated bacteria. Escherichia coli demonstrated high levels of resistance to tested antibiotics, signifying the presence of resistant strains in Malaysia. The antibiotic impact factor calculated was 31.14 for cephalexin, 30.83 for amoxicillin/clavulanic acid, 19.82 for enrofloxacin and 19.43 for ceftriaxone. This study highlights the significance of urine culture and susceptibility testing prior to antibiotic administration. Based on the results of this study, empirical treatment can be provided based on the bacterial spectrum and the antibiotic impact factor.